The Axial Age and its consequences - Bellah, Robert N. (Belknap Press, 2012)
Intro -- Contents -- Introduction - Robert N. Bellah and Hans Joas -- Fundamental Questions -- 1. The Axial Age Debate as Religious Discourse - Hans Joas -- 2. What Was the Axial Revolution? Charles Taylor -- 3. An Evolutionary Approach to Culture: Implications for the Study of the Axial Age - Merlin Donald -- 4. Embodiment, Transcendence, and Contingency: Anthropological Features of the Axial Age - Matthias Jung -- 5. The Axial Age in Global History: Cultural Crystallizations and Societal Transformations - Björn Wittrock -- 6. The Buddha's Meditative Trance: Visionary Knowledge, Aphoristic Thinking, and Axial Age Rationality in Early Buddhism - Gananath Obeyesekere -- 7. The Idea of Transcendence - Ingolf U. Dalferth -- A Comparative Perspective -- 8. Religion, the Axial Age, and Secular Modernity in Bellah's Theory of Religious Evolution - José Casanova -- 9. Where Do Axial Commitments Reside? Problems in Thinking about the African Case - Ann Swidler -- 10. The Axial Age Theory: A Challenge to Historism or an Explanatory Device of Civilization Analysis? With a Look at the Normative Discourse in Axial Age China - Heiner Roetz -- Destructive Possibilities? -- 11. The Axial Conundrum between Transcendental Visions and Vicissitudes of Their Institutionalizations: Constructive and Destructive Possibilities - Shmuel N. Eisenstadt -- 12. Axial Religions and the Problem of Violence - David Martin -- 13. Righteous Rebels: When, Where, and Why? - W. G. Runciman -- Reevaluations -- 14. Rehistoricizing the Axial Age - Johann P. Arnason -- 15. Cultural Memory and the Myth of the Axial Age - Jan Assmann -- Perspectives on the Future -- 16. The Axial Invention of Education and Today's Global Knowledge Culture - William M. Sullivan -- 17. The Future of Transcendence: A Sociological Agenda - Richard Madsen.